2018
DOI: 10.1016/j.pgeola.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Rifts, rivers and climate recovery: A new model for the Triassic of England

Abstract: Triassic basins of England developed under a regime of largely WE extension and progressed from non-marine fluvial and aeolian sedimentation (Sherwood Sandstone Group), through semi-marine playa lacustrine deposits (Mercia Mudstone Group) to fully marine environments (Blue Anchor Formation and Penarth Group). A new tectono-stratigraphic model for the Sherwood Sandstone Group is proposed in which two major long-distance river systems developed under conditions of relative fault inactivity in the Early Triassic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 85 publications
0
36
0
Order By: Relevance
“…This arid zone unit may in fact have greater affinity with the Nettlecombe Formation (Figure b), an anhydritic playa lacustrine deposit that overlies the Budleigh Salterton Pebble Beds and accumulated in the hanging wall basin of the Wynford‐Hooke Fault during a time of relatively active extension. Using tectono‐stratigraphic principles, Newell () suggested that the Nettlecombe Formation is a possible correlative of the Wildmoor Sandstone and Wilmslow Sandstone formations of the English Midlands. Both these units include extensive aeolian deposits and may have been deposited during a relatively arid climatic phase in the late Early Triassic that occurred between the two major long‐distance river systems of the Budleigh Salterton Pebble Beds and the Otter Sandstone Formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This arid zone unit may in fact have greater affinity with the Nettlecombe Formation (Figure b), an anhydritic playa lacustrine deposit that overlies the Budleigh Salterton Pebble Beds and accumulated in the hanging wall basin of the Wynford‐Hooke Fault during a time of relatively active extension. Using tectono‐stratigraphic principles, Newell () suggested that the Nettlecombe Formation is a possible correlative of the Wildmoor Sandstone and Wilmslow Sandstone formations of the English Midlands. Both these units include extensive aeolian deposits and may have been deposited during a relatively arid climatic phase in the late Early Triassic that occurred between the two major long‐distance river systems of the Budleigh Salterton Pebble Beds and the Otter Sandstone Formation.…”
Section: Discussionmentioning
confidence: 99%
“…The coastal outcrop of the Otter Sandstone Formation near Sidmouth in south Devon is the most southerly exposure of the parent Sherwood Sandstone Group in onshore England (Figure ). Traced northward from the south Devon coast, the Sherwood Sandstone Group crops around the periphery of a series of linked extensional basins that include the Wessex Basin, the Worcester Graben, and Cheshire Basin (Figure ; Newell, ). At subcrop in southern Britain, the Sherwood Sandstone Group forms a N–S‐trending belt that cuts between the Welsh Massif and London‐Brabant Massif before bifurcating around the Pennines to extend into the East Irish Sea Basin and onto the East England Shelf.…”
Section: Background To the Otter Sandstone Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lithostratigraphic scheme and nomenclature of the Permo‐Triassic succession in sedimentary basins of Great Britain (based on Ambrose, Hough, Smith, & Warrington, ; N. S. Jones & Ambrose, ; Holliday, Jones, & McMillan, ; Hounslow & McIntosh, ; Hounslow & Morton, ; Hounslow & Ruffell, ; Hounslow et al, ; Newell, ) [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Geological Framework Of the Triassic Of Great Britainmentioning
confidence: 99%
“…A paucity of diagenetic studies, which might have been useful for the reconstruction of burial depths, means that tectonic subsidence rates of other Triassic basins in England are poorly constrained. However, the thickness of the Sherwood Sandstone succession in each Triassic sedimentary basin is well constrained by the availability of numerous seismic lines and boreholes (Allen et al, ; Ambrose et al, ; Edmunds & Smedley, ; Kattenhorn & Pollard, ; Newell, , ; Nirex, ). Furthermore, the age (Induan–Ladinian) of the Triassic Sherwood Sandstone Group succession is known from radiometric and palaeomagnetic dating, as well as stratigraphic relationships with adjacent units (Ambrose et al, ; British Geological Survey, ; Hounslow & McIntosh, ; Warrington et al, ).…”
Section: Geological Framework Of the Triassic Of Great Britainmentioning
confidence: 99%